Political skill in organizations: paths of an evolving concept - Moraes, Romulo Matos de; Istoe, Rosalee Santos Crespo; Miranda , Valtair Afonso (Revista de Administração da UFSM, 2023)
Purpose: To present a scientific mapping of the concept of Political Skill in Organizations and its measurement instrument to show how production has evolved, which themes cover this field, trends, and a global panorama of collaborations. Methodology: Statistical methods to delineate the structure of the scientific field and its dynamics. We used the RStudio (Bibliometrix package) and Vosviewer tools to examine metadata from two samples from the Scopus database (n1=797 and n2=807), covering the last 40 years of production on the subject. Findings: Political Skill in Organizations is a current and well-structured construct; its relationship constantly expands with several other concepts; its driving themes are job performance, power, and organizational politics. Emerging topics are stress, impression management, and leader political skill. We also highlighted the most influential authors and publications. The Political Skill Inventory measurement instrument remains widely used in different contexts. However, there need to be more collaborations in Latin America. Originality: An up-to-date analysis of the paths and scope of a concept in conjunction with its measurement instrument promotes theoretical-empirical integration and provides insights and starting points for researchers interested in organizational politics.